Mapping the local dielectric constant of a biological nanostructured system - Valeriano, Wescley Walison; Andrade, Rodrigo Ribeiro; Vasco, Juan Pablo; Malachias, Angelo; Neves, Bernardo Ruegger Almeida; Guimarães, Paulo Sergio Soares; Rodrigues, Wagner Nunes (Beilstein Journal of Nanotechnology, 2021)
The aim of this work is to determine the varying dielectric constant of a biological nanostructured system via electrostatic force microscopy (EFM) and to show how this method is useful to study natural photonic crystals. We mapped the dielectric constant of the cross section of the posterior wing of the damselfly Chalcopteryx rutilans with nanometric resolution. We obtained structural information on its constitutive nanolayers and the absolute values of their dielectric constant. By relating the measured profile of the static dielectric constant to the profile of the refractive index in the visible range, combined with optical reflectance measurements and simulation, we were able to describe the origin of the strongly iridescent wing colors of this Amazonian rainforest damselfly. The method we demonstrate here should be useful for the study of other biological nanostructured systems.
Keywords: dielectric constant; electrostatic force microscopy (EFM); natural photonic crystals; relative permittivity; structural colors